1985
DOI: 10.1111/j.1399-3054.1985.tb02373.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cold, anoxia and ethylene on the flowering ability of buds of Cichorium intybus

Abstract: Come, D. 1985. Effect of cold, anoxia and ethylene OD the flowering ability of buds of Cichorium intybus, -Physiol. Plant. 65:146-150.The apical bud and the axillary buds of Witloof chicory {Cichorium intybus L. cv. Tardive d'Anvers) retnain iti the vegetative state if they are left on the root and maintained at 18°C. Flowering occurs in long days of 16 h after a pretreatment of either S weeks at 3^C, 3 days in cotnplete anoxia at 15°C, or 4 days in the presence of ethylene (1000 pptn) at 15°C. In contrast, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Root pruning has also been shown to promote flowering in wellknown woody species (Meilan, 1997) and in Cymbidium niveo-marginatum (Kostenyuk et al, 1999). In addition, the continual rooting of apices in Cichorium (Joseph et al, 1985) and tobacco (McDaniel, 1980;McDaniel and Hartnett, 1993) prevented flowering. Possibly this could be attributed to the presence in roots of substances inhibitory to flowering, as McDaniel (1996) reported a specific signal in tobacco roots which prevented flowering.…”
Section: Discussionmentioning
confidence: 96%
“…Root pruning has also been shown to promote flowering in wellknown woody species (Meilan, 1997) and in Cymbidium niveo-marginatum (Kostenyuk et al, 1999). In addition, the continual rooting of apices in Cichorium (Joseph et al, 1985) and tobacco (McDaniel, 1980;McDaniel and Hartnett, 1993) prevented flowering. Possibly this could be attributed to the presence in roots of substances inhibitory to flowering, as McDaniel (1996) reported a specific signal in tobacco roots which prevented flowering.…”
Section: Discussionmentioning
confidence: 96%
“…The switch from one lifecycle to another may involve spatial regulation of gene expression. Chicory is a species in which vernalization of the adult plant is perceived by the root collar and not by the bud, as reported for the witloof variety (Joseph et al ., ). The bienniality of chicory may therefore involve a combination of developmental and spatial regulation of genetic repressors of flowering such as CiFL1 .…”
Section: Discussionmentioning
confidence: 97%
“…Joseph et al 46 gave a procedure to extract the cytokinins of chicory root. GLC analysis of purified extract indicated that t‐zeatin, 2‐Isopentenyl adenine (2IP), their respective ribosides and ribotides and t‐zeatin and t‐ribosyl‐zeatin glycosides were present in chicory root 46…”
Section: Cultivation Agricultural Practices Fertilisation Pest Conmentioning
confidence: 99%
“…Verger72 showed that cold treatment increases free cytokinins in tRNAs in the roots. The addition of zeatin riboside (10 −6 M ) to the culture medium increases the flowering ability of explants 46. Many authors have studied in vitro flowering from root fragments of C intybus L, analysing endogenous variations in phenolic compounds, free cytokinins and cytokinins in tRNAs during thermic or photoperiodic treatments 73.…”
Section: Biotechnological Studies; Fundamental and Applied Aspectsmentioning
confidence: 99%